Tip optofluidic immunoassay: Evaluating COVID-19 antibody protection with 1 μL fingertip blood - Xiaotian Tan; Yujuan Chai; Ruihan Li; Binmao Zhang; Hao Li; Jie Zhang; Tianen Zhu; Weishu Wu; Lixiang An; Shi Hu; Bin Yang; Li Wang; et al. (hLife, 2025)
Infectious diseases such as coronavirus disease 2019 (COVID-19) continue to pose significant global health challenges. Effective management of reinfection risks depends on sustained levels of binding and neutralizing antibodies. However, conventional methods—such as enzyme-linked immunosorbent assays (ELISA) and virus neutralization tests (VNT)—are limited by complex workflows, long assay durations, and high sample volume requirements, making them less suitable for routine, decentralized, or time-sensitive surveillance. This study presents a custom-developed tip optofluidic immunoassay (TOI) platform that enables rapid, multiplexed antibody profiling using only 1 μL of fingertip blood. The system integrates batch-fabricated microfluidic immunoreactors with a portable chemiluminescent imaging station, completing both binding and neutralization capability assessments within 40 min. TOI achieves a broad dynamic range (3–4 orders of magnitude), high signal-to-noise ratio (∼10,000), and excellent sensitivity for immunoglobulin G (IgG) detection. A renovated version of the rapid in vitro inhibition assay (RIVIA) is incorporated to evaluate neutralizing antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with greater speed and cost-efficiency. In clinical studies, TOI successfully quantified antibody protection against multiple variants, identifying individuals with broad-spectrum immunity to both wild-type and XBB strains. With its high-precision, rapid turnaround, and minimal sample requirement, TOI offers a valuable tool for decentralized immune surveillance and personalized immunization strategy development.